Epiphrenic esophageal diverticulum in an adolescent with a history of a Nissen fundoplication: A case report - Caitlin A. Fitzgerald; Jeremy G. Fisher; Matthew T. Santore (Elsevier, 2015)
Epiphrenic esophageal diverticuli (EED) are exceedingly rare in children. While esophageal dysmotility is often associated with this diagnosis in adults, the few reports in children implicate retained foreign bodies as the cause. The patient presented here is an 18 year-old female with a distant history of a Nissen fundoplication who developed dysphagia, gastroesophageal reflux, and weight loss, and was found to have an EED. Her symptoms completely resolved following laparoscopic diverticulectomy and hiatal hernia repair. Though the exact etiology of her EED remained unclear, it may have been related to her fundoplication. This potential late complication may be seen more frequently as a large number of children with a history of fundoplication are reaching adulthood.